EDUKASI PENDIDIKAN ANTI BULLYING DALAM PERSPEKTIF ISLAM DI SEKOLAH MAPN (MADRASAH ALIYAH PERSIAPAN NEGERI) 4 MEDAN - Hidayat, Rahmat; Thaib, Zamakhsyari Bin Hasballah; lubis, Muya Syaroh Iwanda (MAJU : Indonesian Journal of Community Empowerment, 2025)
This community service activity was motivated by the increasing number of bullying cases in schools, which negatively impacts students' psychological development and academic achievement. Bullying not only causes physical injuries but also long-term mental trauma. Therefore, a comprehensive approach is needed, one of which is through anti-bullying education based on Islamic values. The goal of this activity is to educate students of MAPN 4 Medan about the dangers of bullying and to foster awareness and mutual respect through an Islamic approach that emphasizes compassion, brotherhood, and justice. Implementation methods include interactive lectures, group discussions, educational video screenings, and role-plays of bullying cases. The results of the activity indicate an increase in students' understanding of the forms of bullying and their impacts, as well as a commitment from students to create a safe, peaceful school environment based on Islamic values. This activity is expected to be the first step in building a school culture free from violence and strengthening students' character within the framework of Islamic teachings.